2003
DOI: 10.1677/jme.0.0300227
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional characterization of a testicular TSH receptor cDNA from the African catfish (Clarias gariepinus)

Abstract: A cDNA encoding a putative thyroid-stimulating hormone receptor (cfTSH-R) was cloned from the testis of the African catfish (Clarias gariepinus). The cfTSH-R showed the highest amino acid sequence identity with the TSH-Rs of other fish species. In addition, an insertion of approximately 50 amino acids, specific for the TSH-R subfamily, was also present in the carboxy terminus of the amino-terminal extracellular domain of the cfTSH-R. Next to the testis and thyroid follicles, abundant cfTSH-R expression was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…We also observed that variation in testis tshb transcript abundance was associated with progression of spermatogenesis, with higher tshb mRNA levels in testes with a greater proportion of mature spermatozoa. Receptors for Tsh have recently been identified in the testicular tissues of several species of teleost fishes, and transcripts for the receptor appear to be localized to the gametes in at least one of these species (Kumar et al 2000, Goto-Kazeto et al 2003, Rahman et al 2003, Vischer & Bogerd 2003, Rocha et al 2007. Transcripts for tshb have also been shown by RT-PCR and in situ hybridization to be present in the testis of another adult teleost: the red-spotted grouper, Epinephelus akaara (Wang et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that variation in testis tshb transcript abundance was associated with progression of spermatogenesis, with higher tshb mRNA levels in testes with a greater proportion of mature spermatozoa. Receptors for Tsh have recently been identified in the testicular tissues of several species of teleost fishes, and transcripts for the receptor appear to be localized to the gametes in at least one of these species (Kumar et al 2000, Goto-Kazeto et al 2003, Rahman et al 2003, Vischer & Bogerd 2003, Rocha et al 2007. Transcripts for tshb have also been shown by RT-PCR and in situ hybridization to be present in the testis of another adult teleost: the red-spotted grouper, Epinephelus akaara (Wang et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that four glycosylation sites are necessary for expression and biologic activity in human TSHR, regardless of location. In contrast, the number of potential N-linked glycosylation sites in the extracellular domain of TSHR was found to be three for C. gariepinus (Vischer and Bogerd, 2003), I. punctatus (Goto-Kazeto et al, 2003), and O. rhodurus (Oba et al, 2000). The relationship between the functionality and the three potential N-linked glycosylation sites in teleosts is still not clear.…”
Section: Discussionmentioning
confidence: 91%
“…In largemouth bass, three of the identified sites, corresponded to NIS (residues 77-79), , and NLT (residues 302-304) of TSHR, confirming that these are highly conserved in teleosts. The first conserved glycosylation site is unique to TSHRs, whereas the other two are also found in other members of the glycoprotein hormone receptor family (Vischer and Bogerd, 2003). It has been reported that four glycosylation sites are necessary for expression and biologic activity in human TSHR, regardless of location.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations